Contrastive Analysis: A Case for Noun Affixes of Indonesia Language and Banten Javanese Language - Hanafi Hanafi (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2020)
This study is aiming to discuss the contrastive analysis of noun affixes of Banten Javanese Language and Indonesian Language. The research method used in this research was qualitative. The technique used in data collection is document study from Indonesian Language and Banten Javanese textbooks used in elementary schools. The data analysis technique used was contrastive analysis by comparing these two languages. This result shows that both Banten Javanese and Indonesian Language have their similarities and differences in terms of noun. The similarities are reflected on prefixes, suffixes, and simulfixes; the differences are reflected on infixes. The result also concludes that the differences may hinder the process of teaching and learning Indonesian Language as L2; the similarities, on the contrary, may serve the facilities to learn Indonesian Language as L2.